Nutrition-specific and sensitive drivers of poor child nutrition in Kilte Awlaelo-Health and Demographic Surveillance Site, Tigray, Northern Ethiopia: implications for public health nutrition in resource-poor settings - Semaw Ferede Abera; Eva Johanna Kantelhardt; Afewrok Mulugeta Bezabih; Alemseged Aregay Gebru; Gebisa Ejeta; Judith Lauvai; Andreas Wienke; Veronika Scherbaum (Taylor & Francis Group, 2019)
Background: Child undernutrition is a prevalent health problem and poses various short and long-term consequences. Objective: This study seeks to investigate the burden of child undernutrition and its drivers in Kilte Awlaelo-Health and Demographic Surveillance Site, Tigray, northern Ethiopia. Methods: In 2015, cross-sectional data were collected from 1,525 children aged 6-23 months. Maternal and child nutritional status was assessed using the mid upper arm circumference. Child's dietary diversity score was calculated using 24-hours dietary recall method. Log-binomial regression and partial proportional odds model were fitted to examine the drivers of poor child nutrition and child dietary diversity (CDD), respectively. Results: The burden of undernutrition and inadequate CDD was 13.7% (95% CI: 12.1-15.5%) and 81.3% (95%CI: 79.2-83.1%), respectively. Maternal undernutrition (adjusted prevalence ratio, adjPR = 1.47; 95%CI: 1.14-1.89), low CDD (adjPR = 1.90; 95%CI: 1.22-2.97), and morbidity (adjPR = 1.83; 95%CI: 1.15-2.92) were the nutrition-specific drivers of child undernutrition. The nutrition-sensitive drivers were poverty (compared to the poorest, adjPR poor = 0.65 [95%CI:0.45-0.93], adjPR medium = 0.64 [95%CI: 0.44-0.93], adjPR wealthy = 0.46 [95%CI: 0.30-0.70], and adjPR wealthiest = 0.53 [95%CI: 0.34-0.82]), larger family size (adjPR = 1.10; 95%CI: 1.02-1.18), household head's employment insecurity (adjPR = 2.10; 95%CI: 1.43-3.09), and residing in highlands (adjPR = 1.93; 95%CI: 1.36-2.75). The data show that higher CDD was positively associated with wealth (OR wealthy = 3.06 [95%CI: 1.88-4.99], OR wealthiest = 2.57 [95%CI: 1.53-4.31]), but it was inversely associated with lack of diverse food crops production in highlands (OR = 0.23; 95%CI: 0.10-0.57]). Conclusions: Our findings suggest that the burden of poor child nutrition is very high in the study area. Multi-sectoral collaboration and cross-disciplinary interventions between agriculture, nutrition and health sectors are recommended to address child undernutrition in resource poor and food insecure rural communities of similar settings.